A solution to the problem of clustered objects compact partitioning; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Pogrebnoy D. V. Dmitrii Vladimirovich; Pogrebnoy A. V. Aleksandr Vladimirovich; Deeva O. V. Olga Vladimirovna; Petrukhina I. A. (2017, 2017)
Title screen